Penggunaan Buku KIA Dengan Pengetahuan Tentang Antenatal Care Pada Ibu Hamil Studi di Wilayah UPT Puskesmas Papar Kabupaten Kediri Provinsi Jawa Timur) - Dewi, Ratna Sari (WELL BEING, 2019)
Use of KIA Handbook less in one of the problems in pregnant women and serial connection with knowledge of Antenatal Care in pregnant women. Territory UPT Puskesmas Papar Kediri East Java Province there are still many pregnant women are lacking in utilizing Use of KIA Handbook as many as 46 respondents. The purpose of this study was to determine the relationship of use KIA book with knowledge of Antenatal Care in pregnant women in the Region UPT Puskesmas Papar Kediri East Java Province. This study design is Analytical Correlation. The population most pregnant women who use the KIA handbook in Region UPT Puskesmas Papar Kediri East Java Province 403 pregnant women. Consecutive sampling technique using sampling with a sample of 80 pregnant women. Instrument research using Check List and Questionnaire. Mann Whitney test. The result showed almost all respondents use KIA book a total of 31 (91,2%), half of the respondents have good knowledge about knowledge of Antenatal Care In pregnant women as much as 39 respondents have good knowledge about knowledge of Antenatal Care in pregnant women as much as 39 respondents (48,75%). Mann Whitney test showed significance p=0.000< 0,05, H1 accepted. It can be concluded that there is a relationship between the use of KIA handbook with knowledge of Antenatal Care in pregnant women in the Region UPT Puskesmas Papar Kediri East Java province. It is expected to improve the knowledge about the use of KIA Handbook and knowledge of Antenatal Care in pregnant women.